2010
DOI: 10.1002/pro.480
|View full text |Cite
|
Sign up to set email alerts
|

Integrated biophysical studies implicate partial unfolding of NBD1 of CFTR in the molecular pathogenesis of F508del cystic fibrosis

Abstract: The lethal genetic disease cystic fibrosis is caused predominantly by in-frame deletion of phenylalanine 508 in the cystic fibrosis transmembrane conductance regulator (CFTR). F508 is located in the first nucleotide-binding domain (NBD1) of CFTR, which functions as an ATP-gated chloride channel on the cell surface. The F508del mutation blocks CFTR export to the surface due to aberrant retention in the endoplasmic reticulum. While it was assumed that F508del interferes with NBD1 folding, biophysical studies of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
141
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(157 citation statements)
references
References 52 publications
15
141
0
1
Order By: Relevance
“…Yet these seemingly similar structures behave in very different ways in terms e.g., of their thermal stabilities and aggregation propensities. [56][57] The importance of this work is two-fold. First it provides new conformations of CFTR at the atomic level which were largely not discussed to date.…”
Section: Discussionmentioning
confidence: 99%
“…Yet these seemingly similar structures behave in very different ways in terms e.g., of their thermal stabilities and aggregation propensities. [56][57] The importance of this work is two-fold. First it provides new conformations of CFTR at the atomic level which were largely not discussed to date.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive chemical and thermal denaturation studies monitored by a variety of biophysical techniques have identified an aggregation-prone, partially unfolded intermediate state on the unfolding pathway that is enhanced by F508del (Richardson et al 2007;Protasevich et al 2010;Wang et al 2010a). F508del does not seem to affect unfolding of this partially unfolded intermediate, suggesting that the F508 region is already unfolded in the intermediate.…”
Section: Dynamics Intrinsic To Cftr Function and Stabilitymentioning
confidence: 99%
“…A recent characterization of these suppressing mutations revealed that their ability to compensate for folding lesions is specific for mutations that mapped within NBD1; mutations located in other domains, including ICL4, which forms an interface with the NBD1 surface, remain dysfunctional even in the presence of the suppressing mutations (34). Furthermore, introduction of these suppressing mutations into bacterially expressed NBD1 improved the soluble protein yield (39), likely through thermodynamic stabilization of the NBD1 fold (40) Together, these data suggest that the STE6-CFTR-āŒ¬F suppressing mutations primarily correct the original lesion in NBD1 caused by āŒ¬F.…”
Section: Discussionmentioning
confidence: 97%